The El Dorado map - O'Hearn, Michael (North Mankato, Minnesota Capstone Young Readers, 2016)
After a stagecoach robbery goes wrong, Cody is arrested and his evil father gets away--but a mysterious man who seems to have magical powers gets him out, and he embarks on a strange journey involving a map to the fabled city of El Dorado, pursued by the Wolf tribe, the Tatanka, his father, and others, all of whom want the map
A gift from book Africa
English stories
1 2 13
NEW_ZTN_GN
Keywords: El Dorado -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction